Emergence of Multidrug-Resistant Salmonella enterica Subspecies enterica Serovar Infantis of Multilocus Sequence Type 2283 in German Broiler Farms - García-Soto, Silvia; Abdel-Glil, Mostafa Y.; Tomaso, Herbert; Linde, Jörg; Methner, Ulrich (Frontiers in Microbiology, 2020)
During the last decade, Salmonella enterica subspecies enterica serovar Infantis (S. Infantis) has become more prevalent across Europe with an increased capability to persist in broiler farms. In this study, we aimed to identify potential genetic causes for the increased emergence and longer persistence of S. Infantis in German poultry farms by high-throughput-sequencing. Broiler derived S. Infantis strains from two decades, the 1990s (n=12) and the 2010s (n=18), were examined phenotypically and genotypically to detect potential differences responsible for increased prevalence and persistence. S. Infantis organisms were characterized by serotyping and determining antimicrobial susceptibility using the microdilution method. Genotypic characteristics were analyzed by whole genome sequencing (WGS) to detect antimicrobial resistance and virulence genes as well as plasmids. To detect possible clonal relatedness within S. Infantis organisms, 17 accessible genomes from previous studies about emergent S. Infantis were downloaded and analyzed using complete genome sequence of SI119944 from Israel as reference. In contrast to the broiler derived antibiotic-sensitive S. Infantis strains from the 1990s, the majority of strains from the 2010s (15 out of 18) revealed a multidrug-resistance (MDR) phenotype that encodes for at least three antimicrobials families: aminoglycosydes (ant(3“)-Ia), sulfonamides (sul1) and tetracyclines (tet(A)). Moreover, these MDR strains carry a virulence gene pattern missing in strains from the 1990s. It includes genes encoding for fimbriae clusters, the yersiniabactin siderophore, mercury and disinfectants resistance and toxin/antitoxin complexes. In depth genomic analysis confirmed that the 15 MDR strains from the 2010s carry a pESI-like megaplasmid with resistance and virulence gene patterns detected in the emerged S. Infantis strain SI119944 from Israel and clones inside and outside Europe. Genotyping analysis revealed two sequence types (STs) among the resistant strains from the 2010s, ST2283 (n=13) and ST32 (n=2). The sensitive strains from the 1990s, belong to sequence type ST32 (n=10) and ST1032 (n=2). Therefore, this study confirms the emergence of a MDR S. Infantis pESI-like clone of ST2283 in German broiler farms with presumably high tendency of dissemination. Further studies on the epidemiology and control of S. Infantis in broilers are needed to prevent the transfer from poultry into the human food chain.